Exploring the role of geospatial technology in disaster management of Batu City: Qualitative analysis using RQDA method - Kriswibowo, Rony; Ramdani, Fatwa; Aknuranda, Ismiarta (Faculty of Computer Science (FILKOM) Brawijaya University, 2021)
Disaster management is important to reduce the risk casualties as well as the environment and economic impacts. One of the stakeholders in disaster management in Indonesia at the local level is the Regional Disaster Management Agency (Badan Pengelolaan Bencana Daerah â€“ BPBD).Â In the process of disaster management, there are several phases. Thi initial phase is known as the prevention phase, which is an attempt to eliminate or reduce the possibility of a threat. In this phase, the role of information technology is important to increase the efficiency in disaster management. One of the information technologies that is used widely in disaster management is the Geographic Information System (GIS). This study explores the role of GIS technology employed at BPBD of Batu City in disaster management. The Research Qualitative Data Analysis (RQDA) method is employed based on the questionnaire data. The results show that the role of GIS technology is very limited. The disaster management at the Batu City is mostly done by the traditional method with the manual approach. The role of technology is limited it needs to be improved. Suggestions for increasing the role of technology is to conduct training on the use of GIS for employees. It is expected to increase the role of technology in disaster management.